(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
The Penal Poles Are Among The New Mechanisms Which Have Been Developed In The Algerian Legislation In The Field Of Penal Investigation In Line With The Enquirements Of International Conventions To Establish Appropriate Measures To Fight The Organized Crime Of All Its Kinds. The Most Important Provisions Of The Algerian Legislation Some Amendments Including The Code Of Penal Procedures And Judicial Organization, The Creation Of Enquiry Authorities Of An Expanded Regional Compentency When It Comes To The Inspection And The Investigation Of Some Crimes Required By The Legislator Exclusively, Owing To The Negative Effects On Internal Stability In Various Spheres. The Penal Poles Have Been Organized Through Legislative Texts That Determined The Local Jurisdiction Rules For All The Four Courts Specialized In Regulation‑ Departure From The General Rule Of This Jurisdiction, As It Defined The Criminal Field Which Is Included Within The Specialization Of These Courts, And These New Procedures That Would As Well Contribute To An Effective And Suitable Monitoring For The Nature Of The Crime. Opening Words - Poles, Investigation, Jurisdiction, Local, Qualitative, Algerian Legislation